Direct Foliar Application of dsRNA Derived From the Full-Length Gene of NSs of Groundnut Bud Necrosis Virus Limits Virus Accumulation and Symptom Expression - Gupta, Dipinte; Singh, Oinam Washington; Basavaraj, Y. B.; Roy, Anirban; Mukherjee, Sunil Kumar; Mandal, Bikash (Frontiers in Plant Science, 2021)
Groundnut bud necrosis virus (GBNV) is the most significant member of the genus Orthotospovirus occurring in the Indian subcontinent. There is hardly any effective measure to prevent GBNV in crop plants. In order to develop GBNV infection prevention procedure, we examined the effect of the direct foliar application of dsRNA derived from the full-length NSs gene (1320 nucleotides) of GBNV. The bacterially expressed dsRNA to the NSs (dsNSs) gene of GBNV was purified and delivered to plants as an aqueous suspension containing 0.01% Celite for evaluating its efficacy in preventing GBNV infection in systemic host, Nicotiana benthamiana as well as in local lesion and systemic host, cowpea cv. Pusa Komal (Vigna unguiculata). The dsNSs application and challenge-inoculation were conducted in three different combinations, where plants were challenge-inoculated with GBNV a day after, immediately, and a day before the application of dsNSs. N. benthamiana plants, which were not treated with dsRNA showed severe systemic wilting and death by 9-16 days post-inoculation (dpi). The non-treated cowpea plants exhibited many chlorotic and necrotic lesions on the cotyledonary leaves followed by systemic necrosis and death of the plants by 14-16 dpi. The dsNSs treated plants in all the combinations showed significant reduction of disease severity index in both N. benthamiana and cowpea. The treatment combination where the GBNV inoculation was conducted immediately after the dsNSs treatment was found to be the most effective treatment in preventing symptom expression. The viral RNA analysis by real time RT-PCR also showed 20 and 12.5 fold reduction of GBNV in cowpea and N. benthamiana, respectively. Our results suggest that the foliar application of dsRNA derived from the full-length NSs gene of GBNV through Celite is successful in delivering long dsRNA leading to effective prevention of GBNV infection.